A security payment model for financial payment using mykad - Ahmad Zahari, Nurul Huda (2011)
The Malaysian Government has created smart national identity card named MyKad for every citizen aged 12 and above since September, 2001. In the following year, the National Registration Department of Malaysia (JPN) has embedded the latest application of MyKad, which is known as Public Key Infrastructure (PKI). It allows secure electronic transactions over the Internet. The electronic transactions include online submission of tax returns, secure email and e-commerce. In parallel with the emergence of e-commerce payment system, a new MyKad Payment Model (MPM) is proposed in order to introduce to the public another function of MyKad that is not only for identification purposes, but also in e-commerce transactions. However, to make this payment model accepted by the public, the focus should be made on two issues; trust/security issue and performance issue. A system with security technique named Arbitrary Random Security Algorithm (ARSA) and a one-to-one multithreading model need to be developed in order to accelerate the authentication response time of MPM. ARSA will automatically change its security algorithm based on times and attacks. If there is no attack or intrusion detected, MPM will wait for the scheduled switching within 30 minutes. However, if attack or intrusion is detected in less than 30 minutes, ARSA will automatically change the security algorithm to a new one. The evaluation of the MPM performance is measured with HP LoadRunner testing tools from which it is found that the response time of MPM with multithreading is better compared to the single thread model and credit card authorisation system. Moreover, the development of ARSA makes this model more secure and safer for the customers.